Colonization and extinction rates estimated from temporal dynamics of ecological communities: The islandr package. Issue 7 (13th April 2019) - Ontiveros, Vicente J.; Capitán, José A.; Arthur, Rohan; Casamayor, Emilio O.; Alonso, David
Abstract: The temporal dynamics of ecological communities are inherently complex, as dispersal processes, interspecific biotic interactions and environmental fluctuations interact to shape species assemblages. We developed an r package, island —a community ecology tool to analyse temporal patterns and explore potential drivers of community dynamics. The r package island is inspired by the simplicity of the Theory of Island Biogeography. Our package includes a suite of functions to easily confront models of increasing complexity to community data from the simplest stochastic model underlying Island Biogeography Theory to more elaborate models that include species responses to environmental variables and imperfect detectability, obtained at regular or irregular sampling times, using maximum‐likelihood and AIC‐based model selection. Models implemented in island should be regarded as simple approximations of true temporal community dynamics. In this sense, we call them effective models which we use to estimate effective parameters . These models are simple, but dynamic, as opposed to purely statistical. We illustrate the concept of dynamic effective models by using an immigration–birth–death stochastic model of population dynamics. We generated simulated community data to demonstrate the correspondence between the underlying true model parameters values and our effective parameter estimates. We present three examples showcasing the uses of our package: detectability estimation and model selection, influence of environmental covariates on community dynamics and estimation of co‐occurrence networks. Three detailed vignettes with a full set of examples accompany the r Package island available on CRAN. Foreign Language Abstract Resumen: La din′amica temporal de las comunidades ecol′ogicas es intr′ınsecamente compleja, ya que procesos como la dispersi′on, interacciones entre especies y fluctuaciones ambientales interactu′an determinando su composici′on. Hemos desarrollado el paquete de R island, una herramienta de ecolog′ıa de comunidades para analizar patrones temporales y estudiar los mecanismos que determinan la din′amica de las comunidades. El paquete island est′a inspirado en la simplicidad de la Teor′ıa de Biogeograf′ıa de Islas. Nuestro paquete contiene funciones que, con datos temporales de comunidad, permiten evaluar f′acilmente modelos de complejidad creciente desde el modelo estoc′astico m′as sencillo de la Teor′ıa de Biogeograf′ıa de Islas hasta modelos m′as elaborados que incluyen respuestas de las especies al ambiente o detectabilidad imperfecta, obtenidos mediante esquemas de muestreo regulares o irregulares, utilizando m′axima verosimilitud y selecci′on de modelos basada en AIC. Los modelos implementados en island deben ser considerados como aproximaciones sencillas a la din′amica temporal real de la comunidad. En este sentido, los denominamos modelos efectivos que utilizamos para estimar par′ametros efectivos. Estos modelos son sencillos, pero din′amicos, en oposici′on a modelos puramente estad′ısticos. Hemos ilustrado el concepto de modelos efectivos din′amicos utilizando un modelo estoc′astico de din′amica poblacional basado en los procesos de inmigraci′on, nacimiento y muerte, mediante el que generamos datos de comunidad simulados para demostrar la correspondencia entre los par′ametros reales subyacentes y nuestras estimas efectivas. Presentamos tres ejemplos mostrando los usos del paquete: estimas de detectabilidad y selecci′on de modelos, influencia del ambiente en la din′amica de la comunidad e identificaci′on de redes de coocurrencia. El paquete island, disponible en CRAN, est′a acompan˜ado con un muestrario de ejemplos en tres detalladas vin˜etas.